2016
DOI: 10.1038/srep20576
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanism realizing sequence-specific recognition of nucleic acids by TDP-43

Abstract: TAR DNA-binding protein 43 (TDP-43) is a DNA/RNA-binding protein containing two consecutive RNA recognition motifs (RRM1 and RRM2) in tandem. Functional abnormality of TDP-43 has been proposed to cause neurodegeneration, but it remains obscure how the physiological functions of this protein are regulated. Here, we show distinct roles of RRM1 and RRM2 in the sequence-specific substrate recognition of TDP-43. RRM1 was found to bind a wide spectrum of ssDNA sequences, while no binding was observed between RRM2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…Conversely, TDP43(ΔRRM2) overexpression increased the risk of death by 42% in comparison to EGFP alone. In light of the ability of RRM1, but not RRM2, to bind RNA in vitro ( Buratti and Baralle, 2001 ; Kuo et al, 2009 ; Furukawa et al, 2016 ), these observations provide strong evidence linking RNA binding to toxicity from TDP43 overexpression.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Conversely, TDP43(ΔRRM2) overexpression increased the risk of death by 42% in comparison to EGFP alone. In light of the ability of RRM1, but not RRM2, to bind RNA in vitro ( Buratti and Baralle, 2001 ; Kuo et al, 2009 ; Furukawa et al, 2016 ), these observations provide strong evidence linking RNA binding to toxicity from TDP43 overexpression.…”
Section: Resultsmentioning
confidence: 85%
“…Notably, the R151A mutation phenocopied the F147L-F149L double mutant closely, while the D247A mutation elicited an intermediate phenotype. Since the majority of high-affinity RNA binding is accomplished by RRM1 ( Buratti and Baralle, 2001 ; Ayala et al, 2005 ; Furukawa et al, 2016 ), TDP43(D247A) may still recognize many conventional TDP43 targets. Supporting this notion, the number of DEGs and alternatively spliced transcripts in cells overexpressing TDP43(D247A) were more similar to TDP43(WT) than other TDP43 variants, and TDP43(D247A) expression dis rupted mitochondrial morphology in rodent primary neurons, albeit less potently than TDP43(WT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have consistently shown preferential binding of TDP-43 to (TG)/(UG) sequences (Buratti et al, 2001;Kuo et al, 2009;Sephton et al, 2011;Colombrita et al, 2012;Bhardwaj et al, 2013;Lukavsky et al, 2013;Furukawa et al, 2016). RRM1 is known to be sufficient and essential for proper nucleic acid binding as its affinity is in the low nanomolar range for the canonical UG-rich sequence, while RRM2 is not (Kuo et al, 2009;Furukawa et al, 2016).…”
Section: The Rna-recognition Motifs (Rrm1-rrm2) Rrm-nucleic Acid Bindingmentioning
confidence: 99%
“…Kuo et al reported a large affinity increase between 4 and 6 nucleotides long, which approximately corresponds to the distance between both nucleic acid binding sites (∼22 Å) (Shodai et al, 2013; Figure 3A). Additionally, the RRMs are connected by a highly flexible loop (178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190)(191), thought to confer adaptability to different nucleic acid partners by allowing different orientations of the RRM domains (Auweter et al, 2006;Furukawa et al, 2016).…”
Section: The Rna-recognition Motifs (Rrm1-rrm2) Rrm-nucleic Acid Bindingmentioning
confidence: 99%